Employment pathways and work‐related issues in head and neck cancer survivors. Issue 4 (10th April 2014) - Koch, Robert; Wittekindt, Claus; Altendorf–Hofmann, Annelore; Singer, Susanne; Guntinas–Lichius, Orlando
Abstract: Background: In this exploratory study, employment and psychological factors were investigated in head and neck cancer survivors with survivorship of ≥2 years. Methods: Fifty‐five head and neck cancer survivors ≤60 years old completed a survey including subscales from the Functional Assessment of Cancer Therapy (FACT) instrument, the Miller Behavioral Style Scale, the General Perceived Self‐Efficacy Scale, the Patient Health Questionnaire‐9 (PHQ‐9), and the Hornheider–Fragebogen short version (HFB) measuring the need for psychological interventions. Exploratory analyses of associations to the employment status were performed. Results: The rate of employed patients dropped from three‐fourths of patients before diagnosis to one‐third at an average of 66.8 months after diagnosis. Current unemployment was associated with harder physical work before cancer diagnosis, surgical treatment, and current risky alcohol consumption. Unemployed survivors reported decreased FACT functional and social well‐being and higher PHQ depression scores. Conclusion: Psychosocial variables were significantly related to employment. Further research is needed to examine these relationships. © 2014 Wiley Periodicals, Inc. Head Neck 37 : 585–593, 2015